2003
DOI: 10.1021/nl0344763
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Separative Enrichment in Metallic or Semiconducting Single-Walled Carbon Nanotubes

Abstract: A postsynthesis method of separating metallic from semiconducting single-walled carbon nanotubes and a method based on absorption spectroscopy for assay of the separation efficiency are described. The separation method relies on chemical discrimination in the charge-transfer complex formation between bromine and the metallic versus semiconducting nanotubes and takes advantage of the resulting density difference to effect a centrifugation-based separation. Calculations support the proposed separation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
244
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(249 citation statements)
references
References 22 publications
4
244
0
1
Order By: Relevance
“…Maeda et al showed that m-SWCNTs could be highly concentrated to 87% by applying a dispersion-centrifugation process in a tetrahydrofuran solution of propylamine. 25 Similar results were also obtained in the m/s separation of SWCNTs by using bromine 26 and porphyrins 27 . The porphyrin and its derivates tend to attach onto the sidewalls of s-SWCNTs, making them enriched in the supernatant.…”
Section: Introductionsupporting
confidence: 73%
“…Maeda et al showed that m-SWCNTs could be highly concentrated to 87% by applying a dispersion-centrifugation process in a tetrahydrofuran solution of propylamine. 25 Similar results were also obtained in the m/s separation of SWCNTs by using bromine 26 and porphyrins 27 . The porphyrin and its derivates tend to attach onto the sidewalls of s-SWCNTs, making them enriched in the supernatant.…”
Section: Introductionsupporting
confidence: 73%
“…[56] These electronic transition differences, however, make SWNT sample homogeneity a major issue. For example, even if a SWNT sample has been separated according to type (met-versus sem-) and d t , [64][65][66][67][68][69][70] different chirality and modality nanotubes will contribute significant heterogeneity as the nanotube diameter gets smaller than 1.5−2 nm. This is expected to play a significant role in the reproducibility of advanced nanotube devices as the community continues the refinement in coupling a variety of biological stimuli to SWNT electronic transitions.…”
Section: Carbon Nanotube Propertiesmentioning
confidence: 99%
“…Advances in the SWNTs growth, [54,55] etching [147] and separation [64][65][66][67][68][69][70] processes could further improve nanotube-uniformity in terms of removing metallic SWNTs. Sem-enriched SWNTs with defined (n, m) chirality can be engineered to have their E ii transitions lined up appropriately with either the thin metal-plasmon resonance or the redox levels of analyte under investigation to further enhance sensitivity.…”
Section: Future Outlook and Concluding Remarksmentioning
confidence: 99%
“…38 These provided potential routes to sort nanotubes by diameter or electronic structure. In our acid-doped samples, we did not observe any hint of such selectivity although this does not rule out the possibility with other dopants.…”
Section: Fig 2 ͑Color Online͒mentioning
confidence: 99%